Integration of Academic and Social Sanctions in Dealing with Sexual Violence on Islamic Campuses - Herdianty Ramlan; Suardi Suardi; Shahrin Bin Hashim (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Sexual violence in higher education institutions is a structural issue that necessitates a multidimensional response. This study aims to analyze the correlation between academic community perceptions regarding the imposition of academic sanctions on students, faculty, and university leaders involved in sexual misconduct. Employing a mixed-method approach, the Research integrates Spearman correlation analysis and thematic analysis of open-ended interviews. The statistical findings reveal strong, significant correlations across the three groups, indicating a shared demand for consistent, non-discriminatory procedural justice. Thematic analysis highlights the substantial role of social sanctions as a mechanism of moral control, particularly when integrated with academic and legal sanctions. The perceived effectiveness of social sanctions is shaped by collective courage and institutional support for victims. Previous literature emphasizes that the legitimacy of sanctions depends on consistency, transparency, and structural accountability. This study contributes both empirical and theoretical insights to reinforce equitable academic sanction systems across hierarchical levels. The findings are relevant for institutional policy development aimed at fostering a safe, dignified, and just campus environment. The study recommends institutional reforms that integrate social and procedural sanctions, as well as comprehensive victim protection in academic settings.